2015
DOI: 10.1002/ccd.26138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute kidney injury classifications in patients undergoing transcatheter aortic valve implantation: Predictors and long‐term outcomes

Abstract: Different clinical characteristics predict the occurrence of AKI after TAVI when RIFLE and KDIGO/VARC-2 classifications are used. Both classification systems of AKI identify patients with increased risk for long-term mortality, with superiority of the KDIGO/VARC-2 definition, which should be used for AKI grading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
4
7
0
1
Order By: Relevance
“…In the current study, AKI rates were 21% with the RIFLE (grade I: 17% and grade III: 0.5%) and 23% with the KDIGO/VARC‐2 classification (grade I: 18%, and grade III: 0.5%), while the discordance between classifications was only 10% . In agreement with previous studies , both classifications showed similar statistical power to independently predict two‐year all‐cause mortality . Despite this unequivocal association between AKI and mortality, we cannot assume causality and it is also conceivable that AKI is a mere marker of comorbidities and frailty.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, AKI rates were 21% with the RIFLE (grade I: 17% and grade III: 0.5%) and 23% with the KDIGO/VARC‐2 classification (grade I: 18%, and grade III: 0.5%), while the discordance between classifications was only 10% . In agreement with previous studies , both classifications showed similar statistical power to independently predict two‐year all‐cause mortality . Despite this unequivocal association between AKI and mortality, we cannot assume causality and it is also conceivable that AKI is a mere marker of comorbidities and frailty.…”
supporting
confidence: 88%
“…Recent studies indicated that small post‐procedural elevations in serum creatinine (≥0.3 mg/dL) portray a bad prognosis, which lead to novel AKI classifications accounting for these tiny changes. In this issue of Catheterization and Cardiovascular Interventions , Koifman et al report the results of a single‐center, observational study elucidating the predictors of two currently used AKI classifications and their prognostic value in 217 patients undergoing TAVI: (a) The RIFLE ( the Risk, Injury, Failure, Loss, and End‐stage Kidney ), thoroughly evaluated since its introduction in 2002 and (b) the KDIGO ( Kidney Disease: Improving Global Outcomes ) from the VARC‐2 ( Valve Academic Research Consortium‐2 ) . In the current study, AKI rates were 21% with the RIFLE (grade I: 17% and grade III: 0.5%) and 23% with the KDIGO/VARC‐2 classification (grade I: 18%, and grade III: 0.5%), while the discordance between classifications was only 10% .…”
mentioning
confidence: 99%
“…The study was aimed to explore the complex interaction between severe CKD and postprocedural AKI to Another relevant section of the manuscript is focused on the predictors of AKI. In accordance to previous studies, 3 as well as peripheral vessels reconstruction could be performed with high interobserver reliability for both annulus and prosthesis sizing. 4 Lastly, the present study emphasizes that half of patients with compromised renal function who underwent TAVR, experiences an immediate postprocedural improvement in kidney function, reporting a decrease in serum creatinine (p = .003).…”
supporting
confidence: 83%
“…Second, we utilized all three accepted clinical definitions for the identification of AKI. Koifman et al demonstrated that the VARC1 and VARC2 classification systems were associated with distinct predictor variables, and that reclassification of AKI grade occurred in approximately 10% of patients when different definitions were applied [18]. Through classification of each patient by the AKIN, VARC1 and VARC2 definitions, we have increased our sensitivity for identifying AKI and ensured that all patients are included in our analysis.…”
Section: Discussionmentioning
confidence: 96%